S107. RANDOMIZED CONTROL TRIAL OF A MOBILE APP-BASED INTERVENTION FOR ADOLESCENTS WITH FIRST-EPISODE PSYCHOSIS: THE THINK APP. (18th May 2020) - Calvo, Ana; Sanchez-Gutierrez, Teresa; Barbeito, Sara; Mayoral, Maria; Moreno, Miguel; Arango, Celso
Abstract: Background: Technological advances in psychiatric treatment is relatively recent. Previous studies have shown an improvement, in the access to treatment, for patients with first-episode psychosis (FEP). This new therapeutic approach may provide patients with personalized, flexible, and evidence-based interventions in their communities and even in their own homes. The aim of this study is to develop and test the effectiveness of a mobile app–based intervention to improve community functioning in adolescents with FEP. Methods: We designed a single-blind randomized clinical trial (RCT) to study the effectiveness of a mobile app–based intervention for adolescents with FEP aged 14–19 years recruited from Gregorio Marañón Hospital, Madrid, Spain. Patients were randomly assigned to an intervention group, which received treatment as usual plus ﬁve modules of a psychological intervention through the mobile app (psychoeducation, recognition of symptoms and prevention of relapses, problem solving, mindfulness, and contact wall), or to a control group (standard care). Results: The effectiveness of the intervention were assessed by means of an extensive battery of clinical tests at baseline and at 3 months of follow-up. The primary outcome was reduction in psychotic and depressive symptoms; secondary outcomes comprise adherence, awareness, use of drugs, and quality of life. Also, will report the usefulness, user experience (UX) and security perceived by adolescents with a PEP: frequency of application use, average time of use, quantitative use, etc. Discussion: To our knowledge, this is the ﬁrst randomized online treatment for adolescent with early psychosis comparison with treatment as usual. The main novelty of our approach is the integration of new technologies with traditional psychoeducation, cognitive behavioral therapy techniques, mindfulness and social skills development.